A biogeographic reversal in sexual size dimorphism along a continental temperature gradient. Issue 4 (16th October 2018) - Tarr, Simon; Meiri, Shai; Hicks, James J.; Algar, Adam C.
Abstract : The magnitude and direction of sexual size dimorphism (SSD) varies greatly across the animal kingdom, reflecting differential selection pressures on the reproductive and/or ecological roles of males and females. If the selection pressures and constraints imposed on body size change along environmental gradients, then SSD will vary geographically in a predictable way. Here, we uncover a biogeographical reversal in SSD of lizards from Central and North America: in warm, low latitude environments, males are larger than females, but at colder, high latitudes, females are larger than males. Comparisons to expectations under a Brownian motion model of SSD evolution indicate that this pattern reflects differences in the evolutionary rates and/or trajectories of sex‐specific body sizes. The SSD gradient we found is strongly related to mean annual temperature, but is independent of species richness and body size differences among species within grid cells, suggesting that the biogeography of SSD reflects gradients in sexual and/or fecundity selection, rather than intersexual niche divergence to minimize intraspecific competition. We demonstrate that the SSD gradient is driven by stronger variation in male size than in female size and is independent of clutch mass. This suggests that gradients in sexual selection and male–male competition, rather than fecundity selection to maximize reproductive output by females in seasonal environments, are predominantly responsible for the gradient.